Replacement of corn by sorghum in diets for pacu juvenile - Sanchez, Milena Souza dos Santos; Nascimento, Marcelo dos Santos; Hisano, Hamilton (Pesquisa Agropecuaria Brasileira, 2016)
The objective of this work was to evaluate the apparent digestibility coefficient (ADC) of sorghum, and to determine the growth performance, somatic indices, hematological parameters, and fillet centesimal composition of pacu juveniles fed diets with different levels of sorghum, besides evaluating the cost of the diet formulation. To determine the ADC of dry matter (DM), crude protein (CP), ether extracts (EE), and gross energy (GE) of sorghum, 160 pacus, with 56.00±8.04 g average weight, were used; fish were fed reference and test diets (30% sorghum) plus 0.1% of chromium III oxide. For the growth performance trial, 180 juvenile pacu (10.80±0.77 g) were used; fish were fed diets containing 0, 25, 50, 75, and 100% replacement of corn by sorghum. The ADC of sorghum by fish were: 78.52% of DM; 74.82% of CP; 94.36% of EE; and 77.24% of GE. There were no differences among diets for the growth performance variables, somatic rates, and hematological parameters. However, for the centesimal composition of fillets, there were differences among treatments. Sorghum shows ADC similar to those of corn and can totally replace it in pacu juvenile diets, besides reducing formulation costs.